2014
DOI: 10.1117/12.2069404
|View full text |Cite
|
Sign up to set email alerts
|

Etched multilayer mask in EUV lithography for 16 nm node and below

Abstract: Etched multilayer masks in EUV lithography for 16 nm node and below are better than conventional binary masks due to their higher image intensities and image slopes. However, aerial-image simulation of etched multilayer masks requires special care in order to obtain accurate results. In this paper, we first show that the usual Hopkins method for partial coherence simulation gives very inaccurate results when off-axis illumination is used. We then discuss an enhanced Hopkins method which provides far greater ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…[3][4][5][6] Moreover, Kim et al also confirmed this observation by numerical analysis. 7,8 However, the mask structure should be taken into account when dealing with the mask fabrication processes, such as patterned mask inspection, 9-13 critical dimension measurement (CD metrology), 14,15 mask repair, 16,17 and cleaning. 18 Takai et al reported that the reduction of the ML stack down to 20 pairs effectively avoided the collapse of the lines by the cleaning process.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Moreover, Kim et al also confirmed this observation by numerical analysis. 7,8 However, the mask structure should be taken into account when dealing with the mask fabrication processes, such as patterned mask inspection, 9-13 critical dimension measurement (CD metrology), 14,15 mask repair, 16,17 and cleaning. 18 Takai et al reported that the reduction of the ML stack down to 20 pairs effectively avoided the collapse of the lines by the cleaning process.…”
Section: Introductionmentioning
confidence: 99%